2008
DOI: 10.3748/wjg.14.7361
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events with bismuth salts for Helicobacter pylori eradication: Systematic review and meta-analysis

Abstract: INTRODUCTIONBismuth salts have been used for centuries in medicine. From a gastroenterology perspective these drugs have been used to treat peptic ulcer disease, dyspepsia, parasitic infections, microscopic colitis, and infectious diarrhoea [1] . The discovery of Helicobacter pylori (H pylori) in 1983 by Warren and Marshall revolutionised the management of peptic ulcer disease [2] , and led to a renewed interest in bismuth compounds, largely because bismuth was found to inhibit the growth of H pylori and was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 45 publications
7
78
1
3
Order By: Relevance
“…The previous study demonstrated that adding bismuth might be a good option to improve the eradication by standard triple therapy apart from increasing the dosage and duration of PPI (Srinarong et al, 2014). Several studies also demonstrated that administration of bismuth in quadruple therapy increased the eradication rate of H. pylori up to 90%, comparing to standard triple therapy (Ford et al, 2008;Fock et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study demonstrated that adding bismuth might be a good option to improve the eradication by standard triple therapy apart from increasing the dosage and duration of PPI (Srinarong et al, 2014). Several studies also demonstrated that administration of bismuth in quadruple therapy increased the eradication rate of H. pylori up to 90%, comparing to standard triple therapy (Ford et al, 2008;Fock et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis on all randomized clinical trials comparing bismuth-based treatments with other treatments were conducted by Ford and colleagues [Ford et al 2008]; 35 randomized clinical trials totalling 4763 patients were identified, and 2435 were treated with bismuth salts. No serious adverse event was reported with the bismuth therapy.…”
Section: Bismuth-based Quadruple Therapymentioning
confidence: 99%
“…Moreover, with the availability of new single (three in one) capsule-containing bismuth substrate, metronidazole, and tetracycline, the number of tablets needs to be taken in the bismuth quadruple group will be substantially decreased and this will also likely increase drug compliance [28]. The only adverse event that occurred with significant frequency was dark stools [29]. In this study, the most adverse reaction of QT was the dark stool, too.…”
Section: Discussionmentioning
confidence: 91%